Inflammatory mediator release following bone grafting in humans: a pilot study - Rhonda D. Preston (Blackwell Synergy, 2007)
Aim: The aim of this pilot study was to track markers of periodontal inflammation and bone resorption associated with decalcified freeze-dried bone allografts. Material and Methods: Eleven subjects completed standardized treatment of intrabony defects X3mm with allografts. Gingival crevicular fluid was collected from the defect site and an adjacent interproximal site within the surgical field at baseline, 2, 4, and 8 weeks post-operatively, and analysed for biochemical markers of inflammation/bone resorption. Probing depth, recession, bleeding on probing, plaque, and 6-month radiographic bone height change were measured. Results: Both prostaglandin E2 (p50.007) and bone-specific type 1 collagen (p50.01) increased in crevicular fluid after 2 weeks in the bone graft sites. Matrix metalloproteinase-9 levels remained constant over time. There were positive correlations between prostaglandin levels during the first 8 weeks and bone height change over 6 months. Conclusions: Periodontal bone grafts stimulate an inflammatory response during the first 2 weeks post-operatively, and the potential negative effects of inhibiting prostaglandins post-operatively should be investigated further.